Professional nurses' experience of violence when nursing mentally ill people in general hospital settings: A phenomenological study - Thandisizwe Redford Mavundia; Marie Poggenpoel; Antoinette Gmeiner (AOSIS, 1998)
Due to a lack of the knowledge and skills required for nursing mentally ill people, professional nurses in general hospital settings tend to not apply appropriate techniques when dealing with mentally ill people. Opsomming Weens die gebrek aan kennis en vaardighede benodig vir die verpleging van geestesversteurde persone, hanteer professionele verpleegkundiges in algemene hospitale geestesversteurde persone sonder bogenoemde kennis en vaardighede. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.